2021
DOI: 10.1200/jco.20.02530
|View full text |Cite
|
Sign up to set email alerts
|

Late Toxicity After Adjuvant Conventional Radiation Versus Image-Guided Intensity-Modulated Radiotherapy for Cervical Cancer (PARCER): A Randomized Controlled Trial

Abstract: PURPOSE Postoperative Adjuvant Radiation in Cervical Cancer (PARCER), a phase III randomized trial, compared late toxicity after image-guided intensity-modulated radiotherapy (IG-IMRT) with three-dimensional conformal radiation therapy (3D-CRT) in women with cervical cancer undergoing postoperative radiation. METHODS Patients were randomly assigned to receive either IG-IMRT or 3D-CRT after stratification for the type of hysterectomy and use of concurrent chemotherapy. The primary end point was 3-year grade ≥ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 32 publications
8
107
1
Order By: Relevance
“…Two trials in gynecological cancer radiotherapy reported lower rates of acute and late toxicity, mainly gastrointestinal and urinary toxicity, with intensity-modulated techniques. Improved patient-related outcomes were observed, while no differences in efficacy outcomes were noted 24 25…”
Section: Quality Of Life and Vaginal Brachytherapymentioning
confidence: 94%
“…Two trials in gynecological cancer radiotherapy reported lower rates of acute and late toxicity, mainly gastrointestinal and urinary toxicity, with intensity-modulated techniques. Improved patient-related outcomes were observed, while no differences in efficacy outcomes were noted 24 25…”
Section: Quality Of Life and Vaginal Brachytherapymentioning
confidence: 94%
“…Although the use of intensity modulated radiotherapy demonstrated a clear difference in physician assessed moderate to severe toxicity, it was observed that the difference in patient reported quality of life was of a lower magnitude. This observation of smaller differences in the two arms in patient reported outcomes on long term follow-up of both PARCER and NRG 1203 suggests that the assessment and reporting of physician and patient reported outcomes are not similar 25 35. Also, patients in different world regions may report quality of life and impact of treatment related symptoms very differently.…”
Section: Impact Of Newer Radiotherapy Techniques On Treatment Related...mentioning
confidence: 96%
“…Therefore, until recently, it was unclear if intensity modulated radiotherapy reduces late (or chronic) gastrointestinal toxicity. PARCER, a phase III randomized controlled trial, compared three-dimensional conformal radiation and intensity modulated radiotherapy in patients receiving postoperative (chemo)radiation for cervical cancer 25. The primary endpoint of the study was physician reported late gastrointestinal toxicity with patient reported quality of life as a secondary outcome.…”
Section: Impact Of Newer Radiotherapy Techniques On Treatment Related...mentioning
confidence: 99%
“…There are benefits and drawbacks to various radiation modalities and techniques depending on the clinical scenario. Intensity-modulated radiation therapy is arguably the standard of care for centers that can offer this therapy for locally advanced cervical cancer, post-operative pelvis cancer, and vulvar cancer 11–13. Although there are fewer uncertainties about the robust delivery of intensity-modulated radiation and it is less expensive than proton therapy, this is generally at the expense of increased low-dose radiation scattered to the rest of the body, which has uncertain clinically meaningful detriment.…”
Section: Development Of Proton Beam Therapymentioning
confidence: 99%
“…A common indication for external beam radiotherapy is for treatment of the post-operative pelvis in patients with uterine and cervical cancer. Currently, the standard of care, where available, is intensity-modulated radiation over three-dimensional conformal radiation therapy based on Radiation Therapy Oncology Group (RTOG) 1203 and the Postoperative Adjuvant Radiation in Cervical Cancer (PARCER) clinical trials 12 13 20. In the former study, investigators randomized 289 women with post-operative uterine or cervical cancer to three-dimensional conformal radiation versus intensity-modulated radiation with or without cisplatin or vaginal brachytherapy boost.…”
Section: Pelvic Radiation: Intensity-modulated Radiation Versus Proto...mentioning
confidence: 99%